INOVASI BETON RAMAH LINGKUNGAN - A Rivai, Masri; Kimi, Sudirman; Revisdah, Revisdah (Universitas Muhammadiyah Palembang, 2019)
In this study the author take Fly Ash and Powder Glass as an added ingredient in the concrete mix. This research intend to know the effect of Fly Ash and Powder Glass on K-300 concrete compressive strenght.This study uses cube-shaped specimens with the siza of 15 x 15 x 15. The total of test specimens in this study as much as 45 sample, each 9 seal of test specimens in 5 condition that is normal, concrete + fly ash 5% + glass powder 18%, concrete + fly ash 5% + glass powder 21%, concrete + fly ash 5% + glass powder 24%, concrete + fly ash 5% + glass powder 27%.After concrete compressive strenght test, the concrete strength og the concrete at age 3, 7 and 28 days with normal condition at 3 days age aqual to 139.26 Kg/Cm2, at age 7 day equal to 202.17 Kg/Cm2 and age 28 day of 307.01 Kg/Cm2. And the value of compressive strength of concrete characteristic with the use of Fly Ash 5% + glass powder 18% has the highest value of concrete compressive strength that is at 3 days age of 151.13 Kg/Cm2, 7 day age equal to 21175 Kg/Cm2 and age 28 is 312.81 Kg/Cm2 . These result exceed the copressive strength values of normal concrete characteristic and show that fly ash and glass powder can increase the compressive of the concrete.